Thyroid markers and body composition predict LDL-cholesterol change in lean healthy women on a ketogenic diet: experimental support for the lipid energy model - Cooper, Isabella D.; Sanchez-Pizarro, Claudio; Norwitz, Nicholas G.; Feldman, David; Kyriakidou, Yvoni; Edwards, Kurtis; Petagine, Lucy; Elliot, Bradley T.; Soto-Mota, Adrian (Frontiers in Endocrinology, 2023)
Background: There is large heterogeneity in LDL-cholesterol change among individuals adopting ketogenic diets. Interestingly, lean metabolically healthy individuals seem to be particularly susceptible, with an inverse association between body mass index and LDL-cholesterol change. The Lipid Energy Model proposes that, in lean healthy individuals, carbohydrate restriction upregulates systemic lipid trafficking to meet energy demands.Objectives: To test if anthropometric and energy metabolism markers predict LDL-cholesterol change during carbohydrate restriction.Methods: Ten lean, healthy, pre-menopausal women who habitually consumed a ketogenic diet for ≥ 6 months engaged in a 3-phase crossover study consisting of continued nutritional ketosis, suppression of ketosis with carbohydrate reintroduction, and return to nutritional ketosis. Each phase lasted 21 days. The predictive performance of all available relevant variables was evaluated with linear mixed-effects models.Results: All body composition metrics, free T3 and total T4, were significantly associated with LDL-cholesterol change. In an interaction model with BMI and free T3, both markers were significant independent and interacting predictors of LDL-cholesterol change. Neither saturated fat, HOMA-IR, leptin, adiponectin, TSH nor rT3 were associated with LDL-cholesterol changes.Conclusions: Among lean, healthy women undergoing carbohydrate restriction, body composition and energy metabolism markers are major drivers of LDL-cholesterol change, not saturated fat, consistent with the Lipid Energy Model.